Focus on critical key technologies: The race for leadership in industry and technology policy - Oliver Falck; Svenja Falk (EconPol Forum, 2024)
Technological sovereignty can be defined as the ability of a country to guarantee access at all times to the key technologies that are necessary to meet social priorities and needs. Despite having different competences, the countries analyzed focus largely on the same fields of technology that are expected to generate value in the future. Measures to promote technological sovereignty are heterogenous across countries and range from the promotion of R&D activities to subsidies for setting up industrial plants. Systematic predictions of technological trends would enable policymakers to deal with new technologies at an early stage and adapt policy measures and institutions.
Keywords: 330